The use of basic counseling skills in individual counseling sessions by counseling guidance students - Dermawan, Oki; Defriyanto, Defriyanto; Busmayaril, Busmayaril; Nisak, Khairun (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study aims to determine the skills and proficiency of Islamic Education Counseling Guidance students in using basic counseling skills in individual counseling sessions. This research uses qualitative research methods with Case Studies research design with multiple case studies. The data collection technique used by the researcher is a purposive sample in data collection techniques using observation, interviews, and documentation. The results showed that Islamic Education Counseling Guidance students used thirteen basic counseling skills: attending, reflection, exploration, confrontation, open-ended questioning, closed-ended questioning, leading, focusing, tentatively concluding, clarifying, facilitating, concluding, and closing. Some basic counseling skills have not been used, such as paraphrasing, minimal encouragement, interpretation, directing, silence, taking the initiative, advice, and information. What carried out the evaluation results after the individual counseling session ended, the counselee was satisfied with the service, and they said they felt helped. The service process provided by the counselor to the counselee will be much more optimal if the counselor or prospective counselor continues to improve their competence and uses all the basic counseling skills that exist in the assistance process.